Inequality in healthcare-seeking behavior among women with pelvic organ prolapse: a systematic review and narrative synthesis - Melese Siyoum; Wondwosen Teklesilasie; Yitateku Alelgn; Ayalew Astatkie (BMC, 2023)
Abstract Introduction Pelvic organ prolapse (POP) affects women's quality of life in various aspects. However, evidence on the healthcare-seeking behavior of women with POP is limited. Therefore, this review aimed to identify and synthesize the existing evidence on the healthcare-seeking behavior among women with POP. Methods This systematic review and narrative synthesis of the literature on healthcare-seeking behavior among women with POP was conducted from 20 June to 07 July 2022. The electronic databases PubMed, African Journals Online, Cumulative Index to Nursing and Allied Health Literature, African Index Medicus and Directory of Open Access Journal, and Google Scholar were searched for relevant literature published from 1996 to April 2022. The retrieved evidence was synthesized using a narrative synthesis approach. The characteristics of included studies and the level of healthcare-seeking behavior were summarized in a table and texts. Error bar was used to show the variability across different studies. Results A total of 966 articles were retrieved of which only eight studies with 23,501 women (2,683 women with pelvic organ prolapse) were included in the synthesis. The level of healthcare-seeking behavior ranges from 21.3% in Pakistan to 73.4% in California, USA. The studies were conducted in four different populations, used both secondary and primary data, and were conducted in six different countries. The error bar shows variation in healthcare-seeking behavior. Conclusions The level of health-care seeking behavior among women with POP is low in low-income countries. There is substantial variability in the characteristics of the reviewed studies. We recommend a large-scale and robust study which will help to better understand the healthcare-seeking behavior among women with POP.